Effects of operating parameters on the performance of washing-electrokinetic two stage process as soil remediation method for lead removal - Ng, Yee Sern; Sen Gupta, B.; Hashim, Mohd Ali (Elsevier, 2015)
The application of washing-electrokinetic two stage process on remediation of lead (Pb) contaminated soil was investigated. The process consisted of an initial soil washing, followed by an electrokinetic process. The use of electrokinetic process in soil washing could provide additional driving force for transporting the desorbed Pb away from the soil even in the absence of pore flow. Thus, high usage of wash solution may be mitigated. In this study, the effect of operating conditions such as electric potential difference, wash solution concentration and initial Pb concentration on the feasibility of washing-electrokinetic two stage process on Pb removal was investigated using response surface methodology based on Box-Behnken design. The wash solution used was citric acid and three main aspects were examined, namely: (i) removal efficiency, (ii) effluent generated, and (iii) power consumption. The results revealed that the increase in electric potential difference and wash solution concentration generally enhanced Pb removal efficiency and the interactions of these parameters were significantly positive. However, undesirable high effluent generation and power consumption were also caused by these increments. Optimisation study revealed that 84.14% removal efficiency with zero effluent generation and a power consumption of 2.27 kW h/kg Pb removed could be achieved at 7.58 V and 0.057 M citric acid concentration. In comparison with normal soil washing, washing-electrokinetic two stage process showed an enhancement in removal efficiency by approximate to 16% via electromigration under optimum conditions using similar solution: soil ratio of <0.8 mL:1 g soil. The study reveals that incorporation of electrokinetic process in soil washing is feasible as it not only enhances Pb removal efficiency at minimum wash solution usage with respect to normal soil washing, but also provides in situ Pb recovery in cathode chamber via electrodeposition. (C) 2015 Elsevier B.V. All rights reserved.